Modern aspects of diagnosis and treatment of cognitive impairments (literature review) - A. B. Lokshina; V. V. Zakharov; N. V. Vakhnina (Неврология, нейропсихиатрия, психосоматика)
Cognitive impairments (CI) are among the most common types of neurological disorders that occur in the practice of both neurologists and doctors of other specialties. The article discusses the modern principles of CI classification according to severity, their clinical signs, diagnostic criteria, and the most important approaches to managing patients with dementia and non-dementia CI. A review of current publications on the treatment of mild CI syndrome (MIS) and dementia was carried out, it was shown that the treatment should be comprehensive and include nondrug methods (regular physical activity, cognitive training), correction of all vascular risk factors, as well as drug treatment aimed at improvement of cognitive functions. At the same time, the strategy for choosing drug therapy for CI is determined by the degree of their severity. The importance of early detection of CI is due to the fact that timely diagnosis of these disorders expands the potential for secondary prevention and therapeutic intervention, which can delay or even prevent the onset of professional and social maladjustment due to the development of dementia. The possibilities of modern neuroprotective and symptomatic therapy of CI, the place of akatinol memantine in the treatment of CI syndrome and dementia are shown. Modern data on the use of this drug in various nosological variants of diseases with MCI syndrome and dementia of varying severity are presented.